2009
DOI: 10.1128/jcm.00491-09
|View full text |Cite
|
Sign up to set email alerts
|

Utility of a Commercially Available Multiplex Real-Time PCR Assay To Detect Bacterial and Fungal Pathogens in Febrile Neutropenia

Abstract: Infection is the main treatment-related cause of mortality in cancer patients. Rapid and accurate diagnosis to facilitate specific therapy of febrile neutropenia is therefore urgently warranted. Here, we evaluated a commercial PCR-based kit to detect the DNA of 20 different pathogens (SeptiFast) in the setting of febrile neutropenia after chemotherapy. Seven hundred eighty-four serum samples of 119 febrile neutropenic episodes (FNEs) in 70 patients with hematological malignancies were analyzed and compared wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
91
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(106 citation statements)
references
References 18 publications
8
91
0
3
Order By: Relevance
“…In some of these studies, the SeptiFast assay was found to be clearly superior, 9,11,21,22 whereas in other studies, both methods displayed either similar sensitivities or the SeptiFast assay compared unfavorably with respect to blood culture. 12,[23][24][25] Differences between studies in terms of patients' characteristics, the spectrum of microorganisms detected, the number of blood culture sets collected, the volume of blood collected for culture, and the presence or absence of ongoing antibiotic therapy at the time of sampling may account for these discrepancies. Inappropriate antimicrobial treatment or delays in starting appropriate treatment are both associated with increased morbidity and mortality in sepsis, particularly in severe cases.…”
Section: Discussionmentioning
confidence: 99%
“…In some of these studies, the SeptiFast assay was found to be clearly superior, 9,11,21,22 whereas in other studies, both methods displayed either similar sensitivities or the SeptiFast assay compared unfavorably with respect to blood culture. 12,[23][24][25] Differences between studies in terms of patients' characteristics, the spectrum of microorganisms detected, the number of blood culture sets collected, the volume of blood collected for culture, and the presence or absence of ongoing antibiotic therapy at the time of sampling may account for these discrepancies. Inappropriate antimicrobial treatment or delays in starting appropriate treatment are both associated with increased morbidity and mortality in sepsis, particularly in severe cases.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, fungal antigen testing is convenient and fast, but it lacks sensitivity and specificity, restricting its use in clinical laboratories. Molecular methods using PCR and real-time PCR techniques are useful for the diagnosis of fungal infection but can detect only one or a few specific pathogens (7,8).…”
mentioning
confidence: 99%
“…Recently available molecular assays aid rapid detection of micro-organisms and improve the diagnostic flow-chart (Peters et al, 2004;Gaibani et al, 2009). Among these, a commercial multiplex real-time PCR (LightCycler SeptiFast Test; Roche Molecular Systems) uses a novel technology that enables the direct detection from blood samples of a wide panel of bacterial and fungal microorganisms commonly involved in systemic infections (Lehmann et al, 2008;von Lilienfeld-Toal et al, 2009). This technique was found to give promising results in the neonatal population with sepsis, particularly when antibiotic treatment is initiated (Mussap et al, 2007;Paolucci et al, 2009;Lucignano et al, 2011).…”
mentioning
confidence: 99%